Organizing schools to encourage self-direction in learners - Skager, Rodney W., 1932- (Advances in lifelong education, 1984)
Summarizes and synthesizes four case studies of schools organized to develop self-direction in students. A theoretical perspective on the origins of self-direction is presented and integrated with the findings. The schools, located in the Federal Republic of Germany, Hungary, the Philippines and the USA were studied by local research teams operating under criteria developed for the research. The book seeks to develop a more accurate perspective on the psychological and behavioral characteristics of self-directed learners and to analyze how schools in four different national contexts are organized for the purpose of promoting self-direction in learners.